Pelatihan Pembuatan dan Penggunaan Mistar Bilangan Bulat Bagi Guru Sekolah Dasar Sedistrik Malind - Astuti; Laurensia Elya Puspita; Paustina Ngali Mahuze; Rival Hanip; Eva Nirtha; Rudolfus Ruma Bay; Andreas Au Hurit; Rusmi (LOSARI DIGITAL, 2026)
Community Service (PKM) is one of the Tridharma of Higher Education that must be implemented by lecturers. Lecturers should be sensitive to the problems that exist around them, especially educational issues. The findings obtained were the difficulty of teaching addition and subtraction, so the PKM team held training on making and using whole number rulers to help teachers explain the concept of addition and subtraction of integers. The goal of PKM is to teach elementary school teachers in Malind District to create media that facilitate teaching integers. The method used is training. Data collection uses documentation and interviews. 3 teachers were selected to represent the 8 participating schools. The results of the interviews showed that the training activity on making and using whole number rulers is useful for teachers in using media when explaining mathematical concepts, raising teachers' enthusiasm for teaching using media so that students are enthusiastic about participating in learning, the need for prizes during mathematics learning so that students are more active and enthusiastic. The results of PKM are that teachers in groups can make and use whole number rulers